Religious Leaders’ Interpersonal Communication in Enhancing Teenagers’ Religious Awareness: Case study at Telaga Zam Zam Mosque, Sidikalang - Capah, Muhammad Yarham Syahputra; Ritonga, Elfi Yanti (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
Teenagers are often influenced by various distractions, generational challenges, and differences in personality, which hinder their religious awareness, including for the teenagers at Masjid Telaga Zam-Zam Sidikalang. This study aims to understand how religious leaders use interpersonal communication to overcome these obstacles and enhance the religious awareness of teenagers. The research focuses on Masjid Telaga Zam-Zam Sidikalang in analyzing the interpersonal communication patterns of religious leaders, the obstacles faced, and the resulting impacts. This study uses a qualitative approach with data collection through in-depth interviews and direct observation. The informants consist of religious leaders and teenagers who are actively involved in religious activities at the mosque. The data obtained were analyzed using triangulation techniques with the data analysis approach of Miles and Huberman (1994), which includes data reduction, data display, and drawing conclusions. The findings of the study show that religious leaders use various interpersonal communication strategies, such as direct dialogue, providing good behavioral examples, group activities, and religious study sessions, to increase the religious awareness of teenagers. Despite the obstacles, such as distractions from social media and generational challenges, the interpersonal communication efforts successfully increased the teenagers' involvement in religious activities, strengthened emotional bonds, and encouraged positive changes in their attitudes and behavior. The implications of this study emphasize the importance of interpersonal communication in shaping teenagers' religious awareness, particularly in the mosque environment. This study contributes to the understanding of how religious leaders can utilize interpersonal communication to overcome challenges in guiding teenagers. Recommendations include the development of more adaptive and personal communication strategies to address the challenges faced by teenagers and to enhance their involvement in religious activities.